Archaeological and dating evidence for the 8.2 ka BP climate event on the island of Gökçeada, Northeast Aegean - Erdoğu, B.; Yücel, N.; Gürçal, E. (Materiale și Cercetări Arheologice, 2022)
he 8.2 ka BP event is one of the most proeminent and abrupt climatic events of the Holocene, showing generally drier and colder conditions for ca. 160 years, but there are also variations in climatic impacts by region. Dating and archaeological evidence indicates that the impact of the climate event varies by region, from large‑scale site abandonment to continued occupation and local adaptation. The dating evidence from Uğurlu on the Island of Gökçeada, Northeast Aegean, shows that there is a clear hiatus in 14C dates between ca. 8220 and 8000 cal BP, corresponding to the 8.2 ka BP climate event. This paper presents dating and archaeological evidence from Uğurlu and discusses the consequences of evidence in terms of the 8.2 ka BP climate event.